Frontlog Cataloging: Using In-Process Records to Reveal Backlogged Collections - Nof, Jasmin (Judaica Librarianship, 2011)
The University of Maryland Libraries have acquired tens of thousands of Judaica volumes during the past decades and continuing to the present. The growth has far exceeded cataloging capacity, resulting in a significant backlog that is invisible to selectors and patrons alike. In order to make these materials available, catalogers at UM Libraries developed procedures that make use of in-process records. These processes have since been applied to other backlogs. This paper describes the procedures and discusses their advantages and disadvantages. Overall, the frontlog approach has resulted in visible benefits to both patrons and librarians.